Occupational Hazard? An Analysis of Birth Outcomes among Physician Mothers - Anupam B. Jena; David Slusky; Lilly Springer (Institute of Labor Economics (IZA), 2023)
Training to become a physician involves long work hours that can be physically demanding, particularly for surgeons. Are birth outcomes of physician mothers affected as a result? Using Texas birth data from 2007-2014, we compared birth outcomes between physicians and another highly educated group, lawyers, and between surgeons and non-surgeon physicians. Further, using a difference-in-differences framework, we examine whether the Accreditation Council for Graduate Medical Education 2011 duty hour reform, which lowered trainee work hours, impacted the birth outcomes of babies born to physicians compared with lawyers. We find that physicians have lower birth weights and shorter pregnancies than lawyers with the results driven by physicians in surgical specialties. However, the duty hour reform appears to not have impacted birth outcomes. Thus, we find that physicians tend to have worse birth outcomes than lawyers and, in this case, the work reform did little to address the difference.
Keywords: I12; J13; J44; K32; 330; physicians; surgeons; birth outcomes; birthweight; pregnancy length; duty hour reform